Penataan Lingkungan Sekolah Yang Kondusif Dan Pengaruhnya Terhadap Hasil Belajar Geografi Siswa Kelas IX IPS SMA Negeri 6 Takalar - Syarif, Erman (LaGeografia, 2020)
True education is the responsibility of parents and teachers. Most parents have high expectations and make the school the foundation of their children's success. The purpose of this study was to determine how the influence of the school environment on the learning outcomes of students of class IX social science at SMA Negeri 6 Takalar. The approach used in this study is a quantitative approach by going through several stages of analysis testing, namely, research instrument testing, prerequisite test analysis and hypothesis testing. The results showed that the school environment had a significant influence on the learning outcomes of students of class IX social science in SMA Negeri 6 Takalar with a contribution of 84.2% while the remaining 15.8% was caused by other factors.